A novel and non-toxic dopamine detection method based on self-polymerisation of dopamine. Issue 1 (1st January 2020) - Gong, Xinghui; Wang, Tong; Zhang, Zhendong; Wei, Xiao
Abstract: In this article, we report a simple, effective, sensitive, non-toxic and environmentally friendly method for the detection of dopamine (DA). This method utilises the property of the self-polymerization of dopamine under alkaline conditions, and gets the concentration of dopamine by measuring the fluorescence intensity of polydopamine (PDA) nanoparticles. And this method only uses NaHCO3 to start the polymerization process, so that the detection experiment becomes simple and inexpensive. The fluorescence intensities of the mixed solution produced at different reaction times and different concentrations were studied. Finally, a good linear relationship was obtained in the range of 1.0-400 μM with a correlation coefficient of 0.9946 and a detection limit of 0.3 μM. The method has high selectivity and important application value for detecting dopamine-related diseases.